Induction of a dominant negative CREB transgene specifically blocks long-term memory in Drosophila. - Yin, J.C.P.; Wallach, J.S.; DelVecchio, M.; Wilder, E.L.; Zhou, H.; Quinn, W.G.; Tully, T. (Cell, 1994)
Consolidated memory after olfactory learning in Drosophila consists of two components, a cycloheximide-sensitive, long-term memory (LTM) and a cycloheximide-insensitive, anesthesia-resistant memory (ARM). Using an inducible transgene that expresses a dominant negative member of the fly CREB family, LTM was specifically and completely blocked only after induction, while ARM and learning were unaffected. These results suggest that LTM formation requires de novo gene expression probably mediated by CREB family genes.